2011
DOI: 10.1097/ta.0b013e3182095c8a
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment and Clinical Implication for Posterolateral Rotatory Instability of the Elbow: Osborne-Cotterill Lesion of the Elbow

Abstract: Osteochondral defect in the posterolateral aspect of the capitellum is an important indicator of PLRI; however, the result of this study suggests ligament reconstruction for those with a large bone defect may not be always successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…This lesion has previously been recognized to have an association with posterolateral rotatory instability . Jeon et al observed that an isolated ligament reconstruction may not be successful in these patients and advised addressing the osteochondral defect, as well as performing a lateral ligament reconstruction . We would agree with their observation.…”
Section: Discussionsupporting
confidence: 77%
“…This lesion has previously been recognized to have an association with posterolateral rotatory instability . Jeon et al observed that an isolated ligament reconstruction may not be successful in these patients and advised addressing the osteochondral defect, as well as performing a lateral ligament reconstruction . We would agree with their observation.…”
Section: Discussionsupporting
confidence: 77%
“…[36][37][38] Trochlear and trochlear notch chondromalacia occurs in throwing athletes with medial instability, 39 while osteochondral injury of the capitellum is a feature of posterolateral rotatory instability. 40 Capitellar cartilage injury also occurs in about 10% of patients with radial head fracture. 41 The type, size and stability are the key elements of any focal cartilage injury that needs to be assessed when deciding on whether to pursue conservative or arthroscopic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Ligament reconstruction techniques in addition to bone defect correction using bone graft were successful in patients with bone defect greater than onefourth of the joint surface. The biomechanical evaluation could be important to determine the exact relevant amount of bone loss secondary to PLRI in order to establish the optimal surgical treatment for this patient population [2,9]. Clark et al described a case of capitellum fracture associated with PLRI.…”
Section: Discussionmentioning
confidence: 99%
“…In 1966, Osborne and Cotterill described a posterior capitellum defect in recurrent elbow dislocation (Osborne-Cotterill lesion) [1][2][3][4]. Posterolateral rotatory instability (PLRI) was, more recently, described by O'Driscoll in 1991 [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation